2018
DOI: 10.1101/441808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generalized displacement of DNA- and RNA-binding factors mediates the toxicity of arginine-rich cell-penetrating peptides

Abstract: Due to their capability to transport chemicals or proteins into target cells, cellpenetrating peptides (CPPs) are being developed as therapy delivery tools. However, and despite their interesting properties, arginine-rich CPPs often show toxicity for reasons that remain poorly understood. Using a (PR)n dipeptide repeat that has been linked to amyotrophic-lateral sclerosis (ALS) as a model of an arginine-rich CPP, we here show that the presence of (PR)n leads to a generalized displacement of RNA-and DNA-binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Taken together, we find that diverse importins suppress poly-GR-induced condensation of TDP-43 or RNA, suggesting that importins could have a broadly protective effect by buffering pathological interactions of poly-GR with other macromolecules, including disease-linked RBPs, nucleic acids, and potentially other interactors reported for R-rich DPRs (Boeynaems et al, 2017;Choi et al, 2019;Fumagalli et al, 2019;Hartmann et al, 2018;Lafarga et al, 2019;Lee et al, 2016;Moens et al, 2019;Zhang et al, 2019b Importins have been identified as strong genetic modifiers of poly-GR-and poly-PR-mediated cellular toxicity in several independent studies in Drosophila and yeast (Boeynaems et al, 2016a;Jovi ci c et al, 2015;Kramer et al, 2018;Lee et al, 2016). Additionally, several proteomic studies have previously identified importins as cellular interactors of poly-GR or poly-PR (Boeynaems et al, 2016a;Lee et al, 2016;Lin et al, 2016).…”
Section: Increasing Importin Concentrations Can Suppress Dpr-induced mentioning
confidence: 60%
See 1 more Smart Citation
“…Taken together, we find that diverse importins suppress poly-GR-induced condensation of TDP-43 or RNA, suggesting that importins could have a broadly protective effect by buffering pathological interactions of poly-GR with other macromolecules, including disease-linked RBPs, nucleic acids, and potentially other interactors reported for R-rich DPRs (Boeynaems et al, 2017;Choi et al, 2019;Fumagalli et al, 2019;Hartmann et al, 2018;Lafarga et al, 2019;Lee et al, 2016;Moens et al, 2019;Zhang et al, 2019b Importins have been identified as strong genetic modifiers of poly-GR-and poly-PR-mediated cellular toxicity in several independent studies in Drosophila and yeast (Boeynaems et al, 2016a;Jovi ci c et al, 2015;Kramer et al, 2018;Lee et al, 2016). Additionally, several proteomic studies have previously identified importins as cellular interactors of poly-GR or poly-PR (Boeynaems et al, 2016a;Lee et al, 2016;Lin et al, 2016).…”
Section: Increasing Importin Concentrations Can Suppress Dpr-induced mentioning
confidence: 60%
“…R-rich DPRs have also been shown to form condensates with polyanions, such as RNA (Boeynaems et al, 2017(Boeynaems et al, , 2019, and the interactions of poly-GR/PR with nucleic acids were proposed to have detrimental consequences on RNAand DNA-based processes and cause heterochromatin abnormalities (Boeynaems et al, 2019;Lafarga et al, 2019;Zhang et al, 2019b). We therefore tested whether importins are also able to suppress the formation of poly-GR/RNA condensates.…”
Section: R-rich Dprs Cause the Formation Of Solid-like Importin Condementioning
confidence: 99%
“…Our results here suggest that the ability for C9orf72 dipeptide repeats to perturb SGs may at least partly result from their binding with the aromatic residues in the low-complexity regions of the protein components such as FUS and/or with nucleic acids within SGs. Indeed, very recently, the C9orf72 dipeptide repeats have been identified to manifest their cellular toxicity by becoming tightly associated with any accessible nucleic acids in cells and consequently to impair all reactions of these nucleic acids [92]. This finding is also supported by the observation that protamine, a sperm-specific small polypeptide with the highest percentage of Arg/Lys content within the animal proteome [93], also manifests similar cytotoxicity as C9orf72 repeats by tight binding to nucleic acids [92,93].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, our study implicates an inhibitory interaction of arginine-rich DPRs with the axonal transport machinery in C9orf72-associated ALS/FTD and thereby points to novel potential therapeutic strategies.3 patient-derived induced pluripotent stem cells (iPSCs) (5,10,11,(14)(15)(16)(17)(18). The arginine-rich DPRs -poly-PR and poly-GR -are potently toxic in numerous disease models (14,(19)(20)(21)(22)(23)(24)(25)(26)(27), and have been shown to cause mitochondrial (28,29) and endoplasmic reticulum stress (26), as well as disturbances in gene expression, RNA processing and translation (14,(30)(31)(32)(33)(34), nucleocytoplasmic transport (21,22,25,35) and the dynamics of membrane-less organelles (36)(37)(38). Whether these effects fully explain the toxicity of arginine-rich DPRs remains unclear.Of the several other genes that have been associated with ALS (39), three encode proteins important for microtubule-based cargo transport: the tubulin isotype α4a (40), the plus enddirected kinesin-1 motor KIF5A (41), and DCTN1, a component of the dynactin complex that activates the minus end-directed motor cytoplasmic dynein-1 (hereafter dynein) (42).…”
mentioning
confidence: 99%
“…3 patient-derived induced pluripotent stem cells (iPSCs) (5,10,11,(14)(15)(16)(17)(18). The arginine-rich DPRs -poly-PR and poly-GR -are potently toxic in numerous disease models (14,(19)(20)(21)(22)(23)(24)(25)(26)(27), and have been shown to cause mitochondrial (28,29) and endoplasmic reticulum stress (26), as well as disturbances in gene expression, RNA processing and translation (14,(30)(31)(32)(33)(34), nucleocytoplasmic transport (21,22,25,35) and the dynamics of membrane-less organelles (36)(37)(38). Whether these effects fully explain the toxicity of arginine-rich DPRs remains unclear.…”
mentioning
confidence: 99%